Shape recovery effect of 4D-printed auxetic structures - Teo, Joel Yi Wei (Nanyang Technological University, 2023)
Unlike conventional materials that thin out when they are stretched, auxetics structures will expand. This phenomenon is known as an exhibition of Negative Poisson's Ratio (NPR). Shape Memory Polymers (SMP) in the form of auxetic structures can be shrunken/expanded on at least 2 dimensions in their rubbery state (above Tg), held at that state when in their glassy state (below Tg) and subsequently reversed into their original form, when put in their rubbery state. This project aims to explore 4D printing with auxetic designs, characterise their properties and most importantly, their ability to exert force when the shape memory effect is triggered. It has experimented with resin formulas mixed with different crosslinkers (PEGDA4, PEGDA9 and PEGDA14) to investigate their effect on the glass transition temperature of SMP to find an appropriate formula for experiment on auxetic structures. The formula settled upon for printing was IBOA-PEGDA14 (mol ratio 90%:10%) with BAPO as its photo initiator. The best structure, among the variety experimented with, for exerting recovery force was the ReEntrant Hexagon structure. As for the highest Negative Poisson Ratio, the Anti-Tetra-Chiral structure provided the greatest transverse: load displacement ratio.